Invasive meningococcal disease in the University of Malaya Medical Centre, Kuala Lumpur, Malaysia. - Raja, N.S.; Parasakthi, N.; Puthucheary, S.D.; Kamarulzaman, A. (2006)
BACKGROUND: Neisseria meningitidis (N. meningitidis) remains the leading worldwide cause of acute bacterial meningitis and fatal sepsis in healthy individuals.